Isolamento, cultivo e criopreservação de folículos ovarianos pré-antrais de catetos (pecari tajacu linnaeus, 1758) - Campos, Lívia Batista (Universidade Federal Rural do Semi-Árido, 2019)
The manipulation of oocytes included in pre-antral ovarian follicles increases the reproductive potential and ensures the conservation of biodiversity. In this sense, the objective was to establish efficient protocols for the isolation, culture and cryopreservation of preantral follicles of peccary (Pecari tajacu). In a first experiment, ovaries of six adult females were assigned to different methods of follicular isolation: enzymatic using collagenase type IV, mechanical using a scalpel blade, and association of both. Among these, the highest amount (P <0.05) of follicles was provided by the enzymatic method (961.7 ± 132.9), which also provided the highest proportion of viable follicles (98.7 ± 0.6%). In addition, the integrity of the follicles obtained by the enzymatic method was confirmed by scanning electron microscopy and by fluorescence (86%) after 24h culture. In the second experiment, the expression of ALK-5 (type I) and BMPRII (type II) receptors was identified in ovarian fragments of hips by means of PCR. Then, in vitro culture of ovarian tissue of six animals for 1 or 7 days with GDF-9 (0, 50, 100 or 200 ng / ml) was performed. The follicles cultured for 7 days with 200 ng / mL of GDF-9 maintained the follicular and oocyte diameter similar to those observed on day 1. Compared to fresh control, the percentage of growing follicles was significantly increased in all the treatments, especially in 200 ng / ml GDF-9 for 7 days. In addition, the presence of 200 ng / ml GDF-9 improved cell proliferation after cultivation. In experiment 3, ovarian tissue was vitrified on solid surface and cryosystem systems with 3 M ethylene glycol (EG), 3 M dimethylsulfoxide (DMSO) or with 1.5 M EG plus 1.5 M DMSO. After vitrification, all treatments were found to have similarly maintained the proportion of viable follicles and the occurrence of cell proliferation. However, all treatments maintained the proportion of normal PFs as the control group (75.6 ± 8.6%), except (P <0.05) those vitrificated by SSV with EG (52.8 ± 5.9%) or the combination of CPAs (54.5 ± 10.4%). Finally, from the analysis of 3-activated caspase expression, only the samples processed by SSV with EG (43.4%) or CPAs (33.4%), as well as those glazed with OTC with EG (46.7%), provided values similar to those found for the fresh control group (36.7%). Considering these results, it is suggested that the enzymatic method is an efficient procedure for the isolation of preantral follicles of peccaries; there are BMPR2 and ALK-5 receptors for GDF-9 in the ovarian cortex and GDF-9 at a concentration of 200 ng / mL is important for the in vitro development of ovarian follicles of this species. Further, vitrification using the OTC method with ethylene glycol (3M) as cryoprotectants is efficient for preservation of ovarian tissue from peccaries
Keywords: Folículos pré-antrais; Foliculogenese e biobancos; Preantral follicles; Folliculogenesis and biobanks; CIENCIAS AGRARIAS::MEDICINA VETERINARIA